The risk of myelodysplastic syndrome and acute myeloid leukemia by metformin use and type 2 diabetes status – a Danish nation-wide cohort study - Emelie C. Rotbain; Klaus Rostgaard; Katja Kaastrup; Stine Ulrik Mikkelsen; Henrik Hjalgrim; Kirsten Grønbæk (Acta Oncologica)
Background and purpose: The treatment options for myelodysplastic syndromes (MDS) and acute myeloid leukemia (AML) have increased recently. However, drug resistance persists and patients who are ineligible for curative treatments still have a very poor prognosis. Previous studies support a general anti-neoplastic effect of metformin, and a recent preclinical investigation has shown that metformin may control the expansion of Dnmt3a clonal hematopoiesis, which is known to precede MDS and AML.